Systemic blood flow in hypertension in a community of African ancestry - Mmopi, Keneilwe Nkgola (My University, 2021)
Hypertension is a particularly important cause of death and disability in groups of African descent, an effect thought to be consistent with the evolutionary theory of antagonistic pleiotropy. In this regard, groups originating from equatorial countries are hypothesized to have evolved to survive fluid losing states through a genetic predisposition to renal fluid retention. Although this prevents fluid loss in hot climates, with aging and excess Na+ intake, fluid accumulation may result in hypertension through an enhanced intravascular volume. However, because of the absence of measurable increases in systemic blood flow in primary hypertension, this hypothesis is not universally accepted. Nevertheless, studies to determine the hemodynamic basis of hypertension in this ethnic group are markedly limited. In the present thesis, in a cross-sectional community based study conducted across the full adult lifespan (aged 16 years and above). I therefore evaluated the hemodynamic basis of hypertension in a group of African descent living in South Africa (SOWETO). As renal fluid retention is thought to increase blood pressure (BP) in response to Na+ intake, I first determined the relationship between 24-hour urinary Na+ and K+ excretion (an index of salt intake) and systemic hemodynamics in 581 randomly selected community participants from SOWETO. Using multivariate adjusted regression analysis, I showed that an abnormal salt intake (indexed by a high Na+ /K+ ) is independently associated with systolic BP (SBP) and pulse pressure (PP) through an enhanced proximal aortic characteristic impedance (resistance to flow in a pulsatile system in the absence of wave reflection [Zc]), but not through changes in peak aortic flow (the product of maximum velocity and the largest diameter in the left ventricular outflow tract in early systole) [Q]). The associations of salt intake with Zc were not accounted for by variations in aortic root diameter and translated into elevated PP and SBP values through an enhanced early central systolic (determined by PQxZc) and hence forward travelling pressure wave (the wave generated from the interaction between maximal flow and impedance to flow in the proximal aorta). These findings therefore suggest that the adverse effects of a high salt intake on BP in groups of African ancestry are through chronic changes in the proximal aorta (aortic stiffness) rather than through an impact of salt intake on renal fluid retention. Although salt intake is not associated with systemic blood flow in groups of African ancestry, this does not exclude a possible alteration in the pressure natriuresis relationship produced by renal effects enhancing systemic blood flow. I therefore determined the age-related iii hemodynamic correlates of blood pressure (BP) across the adult lifespan in 824 participants from the community sample of African ancestry in SOWETO. In multivariate linear regression analysis, independent of confounders, a strong positive association between age and stroke volume (SV), cardiac output (CO) and peak aortic Q, but not with systemic vascular resistance (SVR) was noted. Age relations with pulse pressure were as strongly determined by aortic Q as by Zc or total arterial compliance (TAC). SV, CO and Q accounted for a marked proportion of age-related increases in BP as determined from both office and ambulatory (24-hour) measurements. Consistent with flow effects on renin secretion, increases in systemic flow accounted for age-related decreases in plasma renin concentrations and were correlated with age-related increases in plasma aldosterone concentrations and the aldosterone-to-renin ratio. Thus, from young adulthood, strong age-related increases in systemic flow account for increases in BP in Africa, and these effects explain low renin hypertension. The extent to which increases in systemic flow across the adult age range account for most forms of primary hypertension (systolic and diastolic as well as isolated systolic hypertension) in Africa is unknown. I therefore subsequently aimed to determine the extent to which effects of systemic blood flow contribute to untreated or inadequately controlled systolic and diastolic as well as isolated systolic hypertension in 725 participants from the SOWETO community. Using multivariate adjusted analysis of covariance, I showed that independent of confounders, compared to those with a normotensive BP, uncontrolled systolic and diastolic hypertension was as strongly associated with Q, SV or CO as with SVR, Zc and TAC. Moreover, independent of confounders, as compared to normotensives, uncontrolled isolated systolic hypertension was more strongly associated with Q, SV and CO than with SVR, but less than with TAC and similar to Zc. Thus, in groups of African ancestry living in Africa, hypertension due to increases in either systolic or diastolic BP is as strongly associated with increases in systemic flow (SV, CO and Q) as with arterial and arteriolar effects (Zc, TAC, SVR). In conclusion, in the present thesis I provide evidence published in the high impact journals Hypertension (2 papers) and Journal of Hypertension (1 paper) to support the evolutionary theory of antagonistic pleiotropy and a shifted pressure natriuresis relationship as a cause of primary hypertension in groups of African descent living in Africa. In this regard, I show that although habitual salt intake does not cause primary hypertension through alterations in systemic blood flow, that age-related increases in systemic blood flow are pathognomonic of most low-renin forms iv of primary hypertension at a community level. These data therefore provide the missing evidence (increases in systemic blood flow) to substantiate the importance of a shifted pressure natriuresis relationship as a cause of primary hypertension proposed by Guyton and colleagues close to 50 years ago.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, 2021